Reduction Defect in Sewing Work Stations by Integrating OTSM-TRIZ and FMEA - M. Hanifuddin Hakim; Moses Laksono Singgih (Institut Teknologi Sepuluh Nopember, 2019)
The problems that occur in PT Sepatu are still many defect products. To improve the quality and reduce the number of defects is to make improvements to the flow of the process by using the DMAI stages. In the Define stage, the determination of the selected critical defect is needle fracture, jump stitch, loose stitch, Upper symmetry, and Upper wrinkling. In the Measure phase, DPMO measurements were carried out at 4028 units and a sigma level of 4.1. In the Analyze stage, analyze complex problems that cause defects in the sewing department using Network of Problem (NoP). The output of Nop in the form of partial solution (Ps) and sub problem (Pb) becomes the FMEA input, which will then be analyzed and measured in the value of the RPN. The potential Failure Mode (s) with the highest RPN score in the FMEA table will be a priority and become the initial input to the OTSM-TRIZ stage procedure. In the Improve phase using 40 selected inventory principles the repair solution performs cleaning and checking the position of the rotary-yarn tip at the start of each shift, gives a sign sticker on the tension ring, makes a tool to check bent needles, conducts employee training and employee skill mapping. From the results of the implementation of recommendations, improvements to the estimated reduction defect of 705 pairs of shoes with sigma 4.3 level